PEMBELAJARAN BERBANTUAN MULTIMEDIA BERDASARKAN COGNITIVE LOAD THEORY PADA PELAJARAN MATEMATIKA SD - Rissa Prima Kurniawati (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2014)
Multimedia is media that combine two or more elements are composed of text, graphics, images, photographs, audio, video, and animation are integrated. In multimedia-assisted learning, students are given the opportunity to learn not only of learning resources such as teachers, but give the opportunity to students to develop better cognitive, creative, and innovative. Cognitive Load Theory is a theory that was introduced as a teaching theory based on the knowledge of human cognitive architecture that we have. The main principle of Cognitive Load Theory is the quality of learning is enhanced if attention is concentrated on the role and limitations of working memory. Three cognitive load in working memory, which is intrinsic cognitive load, Germany cognitive load, and extraneous cognitive load. Keywords: Multimedia, Cognitive Load Theory, intrinsic cognitive load, Germany cognitive load, and extraneous cognitive load.